PANELالإفريقية باستعمال معطيات أثر ميازن المدفوعات على النمو الاقتصادي دارسة قياسية لبعض الدول - محمد سعيد رحمون (جامعة البليدة2؛كلية العلوم الاقتصادية العلوم التجارية وعلوم التسيير, 2025)
هدفت هذه الدارسة إلى قياس أثر ميازن المدفوعات على النمو الاقتصادي في عدد من الدول الإفريقية مع ما تشهده دول القارة من تحديات تواجه اقتصاداتها في ظل ، )2023-1990( خلال الفترة ما بين تقلبات الاقتصاد العالمي، تم الاعتماد على منهجية تحليلية تجمع بين الدارسة النظرية والتطبيقية، حيث تناول الفصل الأول الأسس النظرية لميازن المدفوعات (تعريفه، مكوناته، نظرياته)، بينما ركز الفصل الثاني ، على العلاقة بين النمو الاقتصادي وميازن المدفوعات من خلال النظريات الكلاسيكية، النيوكلاسيكية ، الكينزي ة والحديثة، مع تحليل تطورهما في الجازئر ا كما شمل الفصل الثالث تحليلااقتصاديا لتطور محددات النمو في بعض الدول المختارة من شمال إفريقيا وإفريقيا جنوب الصحارء، بينما اعتمد الفصل الاربع على .)Panel ARDLالديناميكية ونموذج ، النماذج القياسية (البانل الساكنة وقد أبان ت الدارسة من خلال التحليل الاقتصادي لتطور محددات النمو الاقتصادي في دول شمال إفريقيا على استقارر نسبي في دول شمال إفريقيا بفضل تنوع الموارد ، وإفريقيا جنوب الصحارء في الفصل الثال ث وارتباطها بالاقتصاد العالمي، عكس دول إفريقيا جنوب الصحارء التي واجهت بعض التقلبات في أداءها الاقتصادي بسبب ا عتما دها الكبير على الموارد الطبيعية، كما أثبتت الدارسة القياسية من خلال نموذج وجود ،CCEMG باستخدام طريقة مقدر متوسط المجموعة للتأثيارت المشتركة والمتاربطة PANEL ARDL تأثير سلبي و ل معنوي ميازن المدفوعا ت ( الحساب الجاري كمؤشر له) على النمو الاقتصادي في المدى الطويل، بينما أظهر الاستثمار الأجنبي والانفتاح ا ا ا اا محدود اا إيجابي كما سجل إجمالي أرس ، لتجاري تأثير المال والا دخار المحلي مساهمة إيجابية كبيرة اا بسبب اا معنوي بينما لم يظهر النمو السكاني تأثير ضعف ، COINTE الاستثمار في العنصر البشري، في حين كانت قيمة معامل تصحيح الخطأ في نموذج دارستنا 1r-gdp)) (94 ) أي ما نسبته 0.9435294 .35294% من اختلال التوازن في النمو الاقتصادي يتم أكدت ، تصحيحه من طرف المتغيارت التفسيرية في نموذج دارستنا بصفة دورية بما يقار ب السنة الواحدة ان النمو الاقتصادي يتأثر بشكل كبير بمتغيارت دارستن ا على المدى الطويل . الكلمات المفتاحية: محددات النمو ، الحساب الجاري ، معطيات البانل ، النمو الاقتصادي ، ميزان المدفوعات .Panel ARDL نموذج ،الاقتصادي IV Abstract: This study aimed to measure the impact of the balance of payments on economic growth in a number of African countries over the period (1990-2023), taking into account the challenges facing the continent's economies in light of fluctuations in the global economy. An analytical methodology combining theoretical and applied study was adopted. The first chapter addressed the theoretical foundations of the balance of payments (its definition, components, and theories), while the second chapter focused on the relationship between economic growth and the balance of payments through classical, neoclassical, and modern theories, with an analysis of their evolution in Algeria. The third chapter included an economic analysis of the evolution of the determinants of growth in a few selected countries in North Africa and sub-Saharan Africa, while the fourth chapter relied on econometric models (static and dynamic panels and the ARDL panel model). Through the economic analysis of the development of the determinants of economic growth in North African and Sub-Saharan African countries in Chapter Three, the study demonstrated relative stability in North African countries due to the diversity of resources and their connection to the global economy, unlike Sub-Saharan African countries, which have faced some fluctuations in their economic performance due to their heavy dependence on natural resources. The econometric study, using the PANEL ARDL model using the CCEMG method, demonstrated a negative and significant impact of the balance of payments (current account as an indicator) on long-term economic growth, while foreign investment and trade openness showed a limited positive impact. Total capital and domestic savings also recorded a significant positive contribution, while population growth did not show a significant impact due to low investment in the human element. Meanwhile, the value of the error correction coefficient in our study model (COINTE 1r-gdp) was (-0.9435294), which represents 94.35294% of the imbalance in economic growth, which is corrected by the explanatory variables in our study model periodically, approximately one year, confirming that economic growth is greatly affected by our study variables in the long run. Keywords: Balance of payments, economic growth, panel data, current account, determinants of economic growth, ARDL Panel.
Keywords: محددات النمو; النمو الاقتصادي; ميزان المدفوعات